ANALISIS TEORI AUSUBEL PADA PENERAPAN MODEL REALISTIC MATHEMATICS EDUCATION DALAM PEMBELAJARAN MATEMATIKA - Muhammad Majdi (Al-Mudarris: Journal Of Education, 2019)
This study aims to find out how the influence of Ausubel's theory on the application of realistic mathematics education models in mathematics learning. This type of research is qualitative descriptive, namely research that describes the conditions that exist in the field. This research was conducted in class IV at MIN 4 Banjarmasin. The result of this research is that the application of RME with cognitive psychology theory can improve students' understanding in mathematics learning.